1984
DOI: 10.1111/j.1348-0421.1984.tb00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Age of Appearance of IgG, IgM, and IgE Antibodies Specific for Loa loa in Gabonese Children

Abstract: IgG, IgM, and IgE antibodies against the filaria Loa loa were measured in umbilical cord blood and in blood from young Gabonese children by an ELISA technique using a homologous metabolic antigen. For children in eight consecutive age groups and adults the percentage of the population positive for each of the antibody classes was determined. The number of children with maternal IgG decreased until one year of age when new synthesis began to become apparent. 1gM antibodies were detected only after six months, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This finding is in accordance with the larger numbers of IgG4‐producing plasma cells in the nodules from patients with generalized onchocerciasis compared to those with the hyperreactive form (Büttner, unpublished data). A continuous synthesis of IgM, an antibody predominating in the early humoral responses to parasite infections, has been reported in Loa loa infection ( Goussard et al . 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with the larger numbers of IgG4‐producing plasma cells in the nodules from patients with generalized onchocerciasis compared to those with the hyperreactive form (Büttner, unpublished data). A continuous synthesis of IgM, an antibody predominating in the early humoral responses to parasite infections, has been reported in Loa loa infection ( Goussard et al . 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated recently that individuals receive 20-24 infective fly bites per year (Noireau et al 1990). In addition, seropositivity is very high, in one hyperendemic zone 95% of the inhabitants had antibodies reacting with L. loa antigens by the age of two years (Goussard et al 1984). Yet, despite heavy exposure to infection the prevalence of microfilaraemia rarely exceeds 30% (Fain et al 1974, Van Hoegaerden et al 1987 and after the age of 20 years the intensity of infection does not increase with age (Kershaw & Nicholas 1954, Noireau et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The second is that a high proportion of parasitised subjects (as determined by signs of apparent infection such as history of eyeworm), do not present with microfilaraemia (although a similar phenomenon is also observed in LF [72]). Indeed, despite high prevalence of apparent infection (history of eyeworm), which in hyperendemic regions can surpass 70% [4], with 95% of the population possessing antibodies reacting with L. loa antigens by the age of 2 years [73], the proportion of people with microfilaraemia (assessed by microscopy) is often far lower, typically representing 30-40% of the total population, and only 50-60% in highly endemic areas (and even then only in adults older than 50 years of age) [70]. It is often, therefore, concluded that a substantial fraction of the population is amicrofilaraemic [74].…”
Section: Prevalence and Intensity Of Infection In Human Populationsmentioning
confidence: 99%